2016
DOI: 10.1097/inf.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Costs of Rotavirus and Other Types of Gastroenteritis in Children in Norway

Abstract: Healthcare costs of rotavirus gastroenteritis in Norway are substantial. The cost-effectiveness of ongoing rotavirus immunization program should be reassessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…In the vaccination strategy, we added the costs of the vaccination programme, including the vaccine itself, and also implementation, administration and storage costs. To compute the costs of primary care consultations more accurately, we differentiated between primary care consultation at emergency outpatient clinics (EOCs) and general practitioner (GP) offices based on proportions reported by Shin et al [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vaccination strategy, we added the costs of the vaccination programme, including the vaccine itself, and also implementation, administration and storage costs. To compute the costs of primary care consultations more accurately, we differentiated between primary care consultation at emergency outpatient clinics (EOCs) and general practitioner (GP) offices based on proportions reported by Shin et al [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of hospitalisation due to RVGE was estimated at three cases per 1000 children below 5 years of age [ 8 ], while the incidence of primary care consultations and homecare disease episodes was derived from the hospitalisation estimates. Since 2009, new and improved studies have assessed the health [ 9 ] and economic [ 10 ] burden of rotavirus in the primary and secondary healthcare sectors in Norway. These studies reported a higher incidence of rotavirus–associated primary care consultations (30.6 per 1000 children) and hospitalisations (6.3 per 1000 children) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vi har ikke tilsvarende undersøkelser av rotavirusinfeksjoner i allmennpraksis, men det er gjort flere kartlegginger av gastroenteritt, oppkast og diaré, basert på regningskort fra fastleger og legevaktleger (3)(4)(5). Gastroenteritt er årsak til 3,6 % av alle konsultasjoner med barn under fem år (5).…”
unclassified
“…Gastroenteritt er årsak til 3,6 % av alle konsultasjoner med barn under fem år (5). De fordeler seg med 28-30 % på legevakt og resten hos fastlege (3)(4)(5). Før innføring av rotavirusvaksine ble det beregnet at omtrent 30 % av tilfellene skyldtes rotavirus (1,2).…”
unclassified
“…The high frequency of development of severe forms of rotavirus gastroenteritis in young children, the difficulties in treating patients, and the negative consequences of the disease (imbalance of the gut microbiota, decreased immune forces of the body, etc.) determine the relevance of this pathology [4,15]. In recent years, the interest of scientists has been attracted by the problem of immunopathogenesis of intestinal infections, including rotavirus etiology, various exogenous and endogenous factors that can change the immune response of patients and, as a result, the clinical manifestations of the disease and its course [3,6,7].…”
mentioning
confidence: 99%